Uso de biofertilizante porcino en el crecimiento inicial de especies arbóreas - Costa, G. A.; de Castro, E. B. [UNESP]; Santos, L. D.T.; Alonso, J.; dos Santos, S. A. [UNESP]; Barros, R. E.; Colen, F. (My University, 2016)
The initial growth of moringa (Moringa oleifera), cañafistula (Peltophorum dubium) and leucena (Leucaena leucocephala) fertilized with increased dose of pig biofertilizer was studied. A complete randomized design with 12 repetitions per treatment was used. The experiment was conducted in the field using a distance of 3 × 3 m for planting and two applications of biofetilizer dose were made at 2 and 11 months after planting, always applied on the surface. For the three species the use of pig biofertilizers was efficient. The growth in height and diameter for moringa, increased linearly with the increasing doses of pig biofertilizer up to the maximum dose (12.4 liters/plant). In case of leguminous species, caña fistula and leucaena, this increase was only found until doses up to 6.2 liters/plant. It is concluded that the use of pig biofertilizers can be efficient in the initial culture of the tree species studied.
Use of pig biofertilizer on initial growth of trees species
Keywords: Leucaena leucocephala; Moringa oleifera; Organic fertilization; Peltophorum dubium; Waste recycling